AN ANALYSIS OF FIGURATIVE LANGUAGE IN LADY GAGA’S SONG LYRICS - Wahab, Abdul; Utami, Ni Made Verayanti; Maharani, Putu Devi (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThis research aimed to analyze figurative language in Lady Gaga song of Chromatica album thatwere released in 2020. There are two problems that are formulated in this study, they are: (1) whatkinds of figurative language found in Lady Gaga song lyrics, (2) what are the meaning of figurativelanguage found in Lady Gaga song lyrics. There are two theories used in this research; the firsttheory proposed by Knickerbocker and Reninger (1963:367) that is used to identify the kinds offigurative language and the second theory is the theory of meaning which supported by Leech(1974) to analyze the meaning. The method used in collecting the data was done by formal andinformal method. The writer collected the data by downloading the song, listening carefully,reading the scripts, underling, and classifying the lyrics which are contain the kinds of figurativelanguage. The method of analyzing data was identifying, analyzing and making conclusions. Thefrequency of each kinds of figurative language was 18,18% contained simile type, 40,90%contained hyperbole type, 13,63% contained metaphor type, 4,54% contained personification type,4,54% contained paradox type, 9,90% contained metonymy type and 9,90% contained allusiontype. The result of meaning in Lady Gaga was conceptual meaning, connotative meaning, affectivemeaning and reflected meaning. It can be concluded that figurative language has important rolesin created the song lyricsKeywords: Figurative language, song lyrics and meaningABSTRAKPenelitian ini bertujuan untuk menganalisis bahasa kiasan dalam lagu Lady Gaga dari albumChromatica yang dirilis pada tahun 2020. Ada dua masalah yang dirumuskan dalam penelitianini, yaitu: (1) jenis bahasa kiasan apa yang ditemukan dalam lirik lagu Lady Gaga, ( 2) apa artibahasa kiasan yang ditemukan dalam lirik lagu Lady Gaga. Ada dua teori yang digunakan dalampenelitian ini; teori pertama dikemukakan oleh Knickerbocker dan Reninger (1963:367) yangdigunakan untuk mengidentifikasi jenis-jenis bahasa kiasan dan teori kedua adalah teori maknayang didukung oleh Leech (1974) untuk menganalisis makna. Metode yang digunakan dalampengumpulan data dilakukan dengan metode formal dan informal. Penulis mengumpulkan datadengan mengunduh lagu, mendengarkan dengan seksama, membaca skrip, menggarisbawahi, danmengklasifikasikan lirik yang mengandung jenis bahasa kiasan. Metode analisis data adalahmengidentifikasi, menganalisis dan membuat kesimpulan. Frekuensi masing-masing jenis majasadalah 18,18% mengandung tipe simile, 40,90% mengandung tipe hiperbola, 13,63%mengandung tipe metafora, 4,54% mengandung tipe personifikasi, 4,54% mengandung tipeparadoks, 9 ,90% mengandung tipe metonimi dan 9,90% mengandung tipe kiasan. Hasil maknadalam Lady Gaga adalah makna konseptual, makna konotatif, makna afektif dan makna refleksi.Dapat disimpulkan bahwa bahasa kiasan memiliki peran penting dalam menciptakan lirik laguKata kunci: Bahasa kiasan, lirik dan makna lagu